BHUVAN SHOME – AN ANALYSIS WITH REFERENCE TO 5 CODES OF ROLAND BARTHES - Anketa, Kumar (International Journal of Psychosocial Rehabilitation, 2019)
Bhuvan Shome is a movie, directed by the renowned Indian Film director Mrinal Sen that revolves arround a male character’s individual transformation by some interesting turn of events. The plot of the is story and its perception by the viewer with leading charecter as a case is taken in the paper. It is an attempt to relook into the hidden meaning in this offbeat Hindi movie following Barthes’ theoretical framework of coding. Roland Barthes have identified five codes to unfold and understand the text in a scene as it signifies. Following content-based analysis, few selected shots and dialogues identified to have multiple meanings are analysed. Bhuvan Shome, the character circumstantially switchs off his costumes from Western to rural Indian attire. These costumes symboliclly undermine his innocence and makes him an epitome of imperfection. His transformed dual persona from modern (period) versus traditionalism are thematic polarities in the story. Some references including western men’s suit, hunter’s dress and dress of Indian rural farmer men and women etc., which portrays the cultural knowledge of Indian lifestyle. The paper presents the application of Barthes five codes on the selected shots that enriches an understanding to the viewer and attempt to disclose the multiple hidden meanings embedded with these codes